2022
DOI: 10.1002/ehf2.13989
|View full text |Cite
|
Sign up to set email alerts
|

Phenylacetylglutamine as a risk factor and prognostic indicator of heart failure

Abstract: AimsTo explore the associations between serum phenylacetylglutamine (PAGln) and chronic heart failure (HF). Methods and resultsTotally 956 subjects were enrolled consecutively from the Department of Cardiovascular Medicine, Ruijin Hospital. Baseline data were obtained from all participants, and 471 stable chronic HF subjects were followed up. Serum PAGln was analysed by liquid chromatography-tandem mass spectrometry. The association between PAGln and basic renal indicators was assessed by simple correlation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
0
16
2
1
Order By: Relevance
“…In recent years, the link between gut microbiota and circulating PAGln has been elucidated in several studies [35,36], especially by Nemet et al, which validates a major role for gut microbiota in PAGln generation in humans [20]. Notably, some literature regarding CVD seems to uncover the destructive role of circulating PAGln [18,19,23,25,[37][38][39]. For instance, PAGln is reportedly associated with the degree of coronary atherosclerotic severity in patients with coronary artery disease, and similar results were obtained in patients with carotid atherosclerosis [18,39].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In recent years, the link between gut microbiota and circulating PAGln has been elucidated in several studies [35,36], especially by Nemet et al, which validates a major role for gut microbiota in PAGln generation in humans [20]. Notably, some literature regarding CVD seems to uncover the destructive role of circulating PAGln [18,19,23,25,[37][38][39]. For instance, PAGln is reportedly associated with the degree of coronary atherosclerotic severity in patients with coronary artery disease, and similar results were obtained in patients with carotid atherosclerosis [18,39].…”
Section: Discussionmentioning
confidence: 90%
“…This suggests that the association between PAGln and HF is robust across different races. For the predictive value of PAGln for cardiovascular events, a small cohort study including 471 patients with HFrEF with a short follow‐up period also showed that elevated PAGln levels are associated with a higher risk of cardiovascular death [25]. Nonetheless, this study did not consider patients with HFpEF, and a detailed dose‐response relationship was not examined (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with chronic kidney disease, serum PAGln levels were associated with all-cause mortality and cardiovascular disease independent of other risk factors [34]. Two recent Chinese studies also highlighted the association between elevated PAGln levels and adverse cardiovascular outcomes in patients with heart failure [35 ▪ ,36]. In cell models, PAGln increased apoptosis, reactive oxygen species production, calcium/calmodulin-dependent protein kinase II, and ryanodine receptor 2 activation but decreased cell viability [37].…”
Section: Fermentation Of Amino Acids By Gut Microbiomementioning
confidence: 99%
“…Elevated PAGln levels have also been associated with a higher risk of cardiovascular death in HF with reduced ejection fraction (HFrEF); however, these studies were limited in size and follow‐up period [8]. Additionally, the association between PAGln and the classical biomarker NT‐proBNP remained to be fully addressed.…”
mentioning
confidence: 99%